Seasonal and geographical variability of nitryl chloride and its precursors in Northern Europe. (17th August 2018) - Sommariva, Roberto; Hollis, Lloyd D. J.; Sherwen, Tomás; Baker, Alex R.; Ball, Stephen M.; Bandy, Brian J.; Bell, Thomas G.; Chowdhury, Mohammad N.; Cordell, Rebecca L.; Evans, Mathew J.; Lee, James D.; Reed, Chris; et al.
Abstract : Measurements of nitryl chloride (ClNO2 ) and its precursors (O3, NO2, particulate chloride) were made in 2014–2016 at three contrasting locations in the United Kingdom: Leicester, Penlee Point and Weybourne. ClNO2 was observed at all sites and in every season, with the highest concentrations between 00:00 and 04:00 GMT. The median nocturnal concentration of ClNO2 ranged between the detection limit (4.2 ppt) and 139 ppt. A clear seasonal cycle, with maxima in spring and winter, and significant differences between locations in the same season were observed. The main source of particulate chloride was sea salt aerosol (including at Leicester, ∼200 km from the coast). In general, ClNO2 levels were controlled by the concentrations of O3 and NO2, rather than by the uptake and reaction of N2 O5 with particulate chloride. Under these conditions, the seasonality and geographical distribution of ClNO2 can be explained in terms of O3 ‐limited and NO2 ‐limited regimes affecting the formation of the N2 O5 precursor. A global version of the GEOS‐Chem model at medium resolution (2° × 2.5°) was not able to fully capture the observed seasonality of ClNO2, mostly because the model overestimated the concentrations of the precursors, particularly of nocturnal O3 . A higher‐resolution (0.25° × 0.3125°) version of GEOS‐Chem showed better agreement with the observations, although it still overestimated ClNO2 concentrations during summer. Abstract : Measurements of nitryl chloride (ClNO2 ) in the United Kingdom show a distinct seasonal cycle and wide geographical distribution. Under conditions where particulate chloride is not a limiting factor, the observed variability of ClNO2 can be explained in terms of O3 ‐limited and NO2 ‐limited chemical regimes. These conditions are typical of large areas of Northern Europe and are particularly relevant for coastal urbanized regions.